PENYULUHAN ONLINE MENGENAI KESEHATAN REPRODUKSI PADA REMAJA - Dian Permata Nasution; Marolop Parlindungan Napitu; Fransius P. Sinaga (Yayasan Nusantara Hasana Berdikari, 2024)
This study explored an online counseling program on reproductive health for adolescents in Indonesia through the Zoom platform, with the aim of increasing knowledge about puberty, contraception, and STI prevention. Pre- and post-tests demonstrated a significant increase in participants' understanding (evidence of improvement from moderate to high knowledge; 95% correct answers on the post-test). Challenges identified included unstable internet connection quality and privacy issues, but active participation was maintained, making this initiative effective in raising awareness and reducing stigma surrounding reproductive health education among adolescents.